+0  
 
0
56
1
avatar

Am i correct please help thank you

 Feb 14, 2020

Best Answer 

 #1
avatar+18974 
+1

             f(x)  =  g(x)

               2x  =  x2 - 3

                 0  =   x2 - 2x - 3

                 0  =  (x - 3)(x + 1)

       Either  x - 3  =  0     or     x + 1  =  0

                        x  =  3     or           x  =  -1

 Feb 14, 2020
 #1
avatar+18974 
+1
Best Answer

             f(x)  =  g(x)

               2x  =  x2 - 3

                 0  =   x2 - 2x - 3

                 0  =  (x - 3)(x + 1)

       Either  x - 3  =  0     or     x + 1  =  0

                        x  =  3     or           x  =  -1

geno3141 Feb 14, 2020

59 Online Users

avatar
avatar
avatar